Peranan Koordinasi Terhadap Produktivitas Kerja Pegawai Pada Kantor Dinas Pekerjaan Umum Provinsi DKI Jakarta - Amanda Morlian (Program Studi Ilmu Administrasi Negara, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam '45 (UNISMA) Bekasi, 2016)
To made the worker productivity in bureaucracy needed efectively coordination. The writer opinion management functions needed bureaucracy system in efficiency and effective public service The work effectively shown to productivity of operational system This research aims: 1) To get answer the question from writer. 2) To get answer so reserach hypotesis.. The result analyse the data obtained a the following result: 1) [Relation] co-ordinate with the work productivity of officer at Office On Duty Public Work of Provency DKI Jakarta very weak 2) Effective coordination happened in officer storey;level in informal atmosphere, on the contrary coordination of leader with the subordinate take place less be effective caused less konsisitennya programs work